A rare case of duodenal ulcer perforation accompanied by Boerhaave syndrome - Dżeljilji, Agata; Rokicki, Wojciech; Rokicki, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Esophageal perforation is the fastest progressing and the most life-threatening disruption of gastrointestinal tract continuity. It must be regarded as an emergency condition that requires early diagnosis as well as very aggressive and rapid implementation of treatment in order to avoid serious complications and death. Methods of treatment for spontaneous esophageal perforation continue to be a matter of controversy. However, all authors emphasize that ultimate success depends largely on the time taken to establish the diagnosis. The authors of this study describe a rare case of duodenal ulcer perforation accompanied by Boerhaave syndrome.